Mission and power : history, relevance and perils - Longkumer, Atola; Sørensen, Jørgen Skov; Biehl, Michael, 1956- (Regnum Edinburgh centenary series, 2016)
"This volume explores the notion of power in relation to Christian mission and critically engages questions such as: What notions of power have informed mission? How have power structures been negotiated between Christian mission and local culture/religions? Which of these manifestations of power are disturbing and counter to the values of the Gospel?"--Back cover